Pengaruh Pendidikan Kewirausahaan Dan Dukungan Akademik Terhadap Niat Kewirausahaan Mahasiswa (Studi Pada Mahasiswa STIEPARI Semarang) - Aurilia Triani Aryaningtyas; Dyah Palupiningtyas (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
The purpose of this research is to analyze the influence of entrepreneurship education and academic support on entrepreneurial intentions of college students. Data from 68 students STIEPARI Semarang is used to test the hypothesized model. Research using saturation sampling techniques and data was collected by questionnaire. The analysis technique used in this research is multiple linear regression. The results showed that entrepreneurship education and academic support in a positive and significant effect on entrepreneurial intentions of college students. Theoretical implications of the results of research supports the theory and existing research. In addition, managerial implications of the results of research suggest the educational institutions to consider entrepreneurship education and academic support as a factor that is important enough to encourage student interest in entrepreneurship.